Analisis User Experience Aplikasi Getcontact dengan Metode HEART Metrics - Fathoni, Fathoni; Mariska, Inneke Via; Saputra, Marco; Epriyanti, Nadia; Anadia, Qothrunnada Wafi; Ibrahim, Ali (STMIK Banjarbaru, 2025)
Issues related to privacy and security in digital communication have become a primary concern in the use of internet-based applications. This study was conducted to evaluate user experiences with the Getcontact application by applying the HEART Metrics framework, which includes the dimensions of satisfaction, engagement, adoption, retention, and task success. Data were collected from 100 respondents through a questionnaire that had been tested for validity and reliability. The results indicate that the overall usability level of the application falls into the high category, with an average score of 77.41%. The adoption and task success dimensions achieved the highest results in the very high category, while other dimensions also showed positive outcomes but still require improvement. This study is expected to serve as a foundation for developing more intuitive application interfaces and features, thereby enabling continuous enhancement of the user experience.Keywords: User Experience; HEART Metrics; Getcontact; Level of Usability; UX Evaluation AbstrakPermasalahan terkait privasi dan keamanan komunikasi digital telah menjadi perhatian utama dalam penggunaan aplikasi berbasis internet. Studi ini dilakukan untuk menilai pengalaman pengguna terhadap aplikasi Getcontact dengan menerapkan pendekatan HEART Metrics, yang mencakup dimensi kepuasan, keterlibatan, adopsi, retensi, dan keberhasilan tugas. Data dikumpulkan dari 100 responden yang disebar melalui kuesioner dan telah diuji validitas dan reliabilitasnya. Hasil penelitian menampilkan bahwa secara keseluruhan tingkat kegunaan aplikas berada pada kategori tinggi dengan nilai rata-rata sebesar 77,41 persen. Dimensi adopsi dan keberhasilan tugas memperoleh hasil tertinggi dalam kategori sangat tinggi, sementara dimensi lainnya menunjukkan hasil yang juga positif namun masih memerlukan peningkatan. Studi ini diharapkan dapat menjadi dasar dalam pengembangan antarmuka dan fitur aplikasi agar lebih intuitif, sehingga pengalaman pengguna dapat ditingkatkan secara berkelanjutan.